Review of ‘Contributions to understanding climate interactions: stratospheric ozone’ by Gennadi Milinevsky, Asen Grytsai, Oleksandr Evtushevsky, and Andrew Klekociuk. (2022) - S. Krakovska (Український антарктичний журнал, 2023)
Review of ‘Contributions to understanding climate interactions: stratospheric ozone’ by Gennadi Milinevsky, Asen Grytsai, Oleksandr Evtushevsky, and Andrew Klekociuk.  (2022). Kyiv, Akademperiodyka, 252 pp. ISBN: 978-966-360-471-8.